Calculation of ultrasonic field distribution radiated by planar transducers - MARKIEWICZ, Anna (Archives of Acoustics, 1984)
This paper presents a method for numerical calculation of amplitude and phase distribution of ultrasonic fields radiated by a planar transducer in the case of the different boundary conditions. Some theoretical consideration are reported that yield to the numerical approach for the investigated problems. Limited number of calculations are presented to illustrate facilities of the progiamme invented for this purpose.